Kepemimpinan Yang Mengelola Emosi, Membangun Lingkungan Kerja Yang Sehat Dan Produktif Pada Dinas Lingkungan Hidup Provinsi Banten - Amandari, Firatna; Saepudin, Eli Apud; Salsabila, Angeliana Artamevia; Lestari , Dina Ayu; Aryanto, Vani Putri; Anaya, Asqi Savira (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Effective leadership in organizations relies heavily on a leader's ability to manage emotions, both in individual and team contexts. This study aims to explore how leadership that is able to manage emotions can build a healthy and productive work environment in the Banten Provincial Environmental Agency. This study used a qualitative approach with in-depth interview techniques and observation of several leaders and staff at the agency. The results showed that leaders who can manage emotions well, such as empathy, self-control, and effective communication, tend to create a more harmonious and supportive work atmosphere. This healthy environment contributes to increased work productivity, employee engagement and overall job satisfaction. This study provides recommendations for leaders in the Banten Provincial Environmental Agency to further develop their emotional intelligence skills to create a culture of emotional intelligence. A more positive and sustainable work environment. From the results of this study, it can be concluded that leadership that manages emotions well plays an important role in creating a healthy and productive work environment at the Banten Provincial Environmental Service. Leaders who have the ability to control their own emotions, empathize, and communicate effectively can build positive relationships with staff and create a conducive work atmosphere. This healthy environment in turn increases employee motivation, job satisfaction and productivity. Therefore, it is important for leaders in the Banten Provincial Environmental Agency to continue to develop their emotional intelligence, both in interactions with the team and in decision-making, in order to achieve optimal performance and sustainability in the organization